PENYEDIAAN PAKAN SILASE DARI TANAMAN UBIJALAR DALAM MENUNJANG SISTEM PERTANIAN BERKELANJUTAN - Reza Prakoso Dwi Julianto; Edyson Indawan; Sri Umi Lestari; Poppy Indri Hastuti (Jurnal Penelitian Pertanian Terapan, 2022)
The study aims to evaluate the response sweet potato clones by pruning to tuber production and silage making experiments. In the field using Split Plot design with 3 replays. Sweet potato clones are placed as plots and pruning periods as the main plot. V₁: Kuningan Putih, V₂: Beta-2, V₃: Kuningan Merah, V₄: BIS-OP-61, V₅: 73-OP-5, V₆: BIS-OP-61-♀-29, V₇: BIS-OP-61-OP-22. The clone sweet potato consists of trimming period ages 90 dap, 120 dap and 150 dap. The result of trimming stroge is then preserved in the form of silage. Silage making as follows: each clons was cut to a size of 3-5 cm, then used to lower the moisture content. Storage is cut, weighed and added tubers according to treatment is: S1= 100% storage, S2 = 90% storage + 10% tubers, S3= 80% storage + 20% tubers, S₄ = 70% storage + 30% tubers. The nutritional value composition of sweet potato silage has of DM 7.07-23.33%, OM 78.04-91.45%, ash 8.57-21.96%, CP 6.90-16.14%,and CF 17.87-57.57% based on dry materials. The value of sweet potato silage of DMD 42.36-63.71%, OMD 38.85-63.64% and TDN 33.24-56.54%.